The decline of self-employment in industrial countries - Heinz Salowsky (Intereconomics, 1978)
The existence of adequate numbers of self-employed persons is regarded as crucial for effective competition. The decline of self-employment which could be registered in all the Western industrialized countries has therefore given rise to concern. This article analyses the corresponding trends over the past 25 years for 14 countries.
Keywords: 330; Private Business